News and Views: Definitions and Characteristics of Genres in Chinese Journalism - Lupano, Emma (Lingue Culture Mediazioni, 2019)
Journalistic genres in China have acquired distinctive characteristics and have shaped original sub-genres that are unique to the local journalistic tradition. While many studies analyzing their characteristics have been written in Chinese, works on the subject in other languages are still scarce. This contribution aims to fill this void by presenting the two main genres in which written journalistic production can be understood, i.e., “news” and “views”, as well as their sub-genres, and showing how they are interpreted in Chinese media studies. The analysis is based on a corpus of recent academic publications that represent the current Chinese scholarly interpretations of local genres of journalism. In doing so, the paper also offers insights on recent theoretical reflections about the functions of journalistic writing in the People’s Republic of China.